2010
DOI: 10.1177/147323001003800306
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Levels in Non-obese First-degree Relatives of Type 2 Diabetes Patients and Non-diabetic Subjects: A 5-Year Follow-up Study

Abstract: This study was designed to investigate adiponectin levels and their relationship to various parameters at baseline and after 5 years in non-obese first-degree relatives of type 2 diabetes patients (FDR group) versus subjects without a family history of diabetes (normal group). Adiponectin levels at baseline were lower in the FDR group versus the normal group. After 5 years, adiponectin levels had fallen significantly in both the FDR (24.3% reduction) and the normal (35.7% reduction) groups. Adiponectin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…In a cross-sectional study among healthy Korean men and women, lower serum adiponectin levels were associated with a family history of diabetes independently of obesity and insulin resistance [39]. Recently, it has been shown that the FDR group had lower adiponectin levels versus the normal group at baseline, and these levels were reduced in both groups over a five year period [40].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study among healthy Korean men and women, lower serum adiponectin levels were associated with a family history of diabetes independently of obesity and insulin resistance [39]. Recently, it has been shown that the FDR group had lower adiponectin levels versus the normal group at baseline, and these levels were reduced in both groups over a five year period [40].…”
Section: Discussionmentioning
confidence: 99%
“…But Dullaart et al included obese and non-obese patients in the study group and it is not clear to what extent the relationship between plasma adiponectin and carotid IMT, in their study, could be explained by other risk factors associated with obesity and metabolic syndrome. Liu, Wang, Cha, Chen, and Ding (2010) found that adiponectin levels were negatively-correlated with carotid IMT in non-obese first-degree relatives of patients with type 2 diabetes, but they did not study the correlation in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 89%
“…Carotid intima–media thickness (cIMT) is a robust independent predictor of macroangiopathy, especially of coronary events and stroke. Several studies have investigated the relation of cIMT and the circulating adiponectin levels, reporting however contradictory results [62,63]. Gasbarrino et al performed a meta-analysis of the studies which investigated the relationship between APN and cIMT.…”
Section: Non-interventional Clinical Research Studiesmentioning
confidence: 99%